Assessing the relationship between nursing process competency and work environment among clinical nurses: a cross-sectional correlational study - Reza Nemati-Vakilabad; Ehsan Kamalifar; Mobina Jamshidinia; Alireza Mirzaei (BMC Nursing)
Abstract Background The healthcare system is under increasing pressure to improve service quality and patient outcomes, with nurses playing a crucial role. They are responsible for about 80% of healthcare services in hospitals, and their proficiency directly influences care quality, patient satisfaction, and complication rates. The work environment also significantly impacts nurses’ ability to perform these competencies, highlighting the need for a comprehensive understanding of these factors in healthcare delivery. This study aims to assess the relationship between nursing process competency and the work environment among clinical nurses. Methods This study utilized a cross-sectional correlational design involving 321 clinical nurses from five teaching hospitals in Ardabil, Iran. Data were collected from April to June 2024 using the Competency of Nursing Process Questionnaire (CNPQ) and a work environment questionnaire. Data analysis was conducted using SPSS version 14, employing descriptive statistics and analytical methods, including Independent sample t-tests, ANOVA, and Pearson correlation, to examine relationships between variables. Results The findings revealed significant relationships between overall competency of nursing process and supportive work conditions, particularly fairness in evaluation (r = 0.388, p < 0.001) and colleague support (r = 0.306, p < 0.001). Hierarchical regression highlighted key predictors, including position (Beta = 0.21, p = 0.03) and fairness and Equality in evaluation (Beta = 0.22, p < 0.001), while implementation of the nursing process negatively impacted competency of nursing process (Beta = -0.56, p < 0.001). Conclusion The findings highlighted the importance of a positive work environment in improving nursing process competency. To foster a thriving nursing workforce and enhance patient care outcomes, healthcare institutions should implement systems to acknowledge nurses’ contributions and encourage open communication that fosters a sense of belonging and value among staff. Additionally, targeted training programs should be provided to focus on the nursing process and skills enhancement, thereby boosting both confidence and competency. Clinical trial number Not applicable.